2023
DOI: 10.1021/acsami.3c12997
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Wound Dressing Based on Biodegradable CuP Nanozymes for Treating Infected and Diabetic Wounds

Yanping Feng,
Lefeng Su,
Zhaowenbin Zhang
et al.

Abstract: Nanozymes, emerging nanomaterials for wound healing, exhibit enzyme-like activity to modulate the levels of reactive oxygen species (ROS) at wound sites. Yet, the solo regulation of endogenous ROS by nanozymes often falls short, particularly in chronic refractory wounds with complex and variable pathological microenvironments. In this study, we report the development of a multifunctional wound dressing integrating a conventional alginate (Alg) hydrogel with a newly developed biodegradable copper hydrogen phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The different optimal pH ranges hinder the crosstalk of multiple enzyme activities. Feng et al developed a novel pH-responsive composite hydrogel (Alg/CuP) based on copper nanozyme for DFU in an alkaline environment. Alg/CuP dressing exhibited CAT-like activity, where abundant O 2 derived from hydrogen peroxide conversion and continuous release of copper ions promoted angiogenesis and accelerated wound repair.…”
Section: Mechanisms Of Nanozymes For Dfu Treatmentmentioning
confidence: 99%
“…The different optimal pH ranges hinder the crosstalk of multiple enzyme activities. Feng et al developed a novel pH-responsive composite hydrogel (Alg/CuP) based on copper nanozyme for DFU in an alkaline environment. Alg/CuP dressing exhibited CAT-like activity, where abundant O 2 derived from hydrogen peroxide conversion and continuous release of copper ions promoted angiogenesis and accelerated wound repair.…”
Section: Mechanisms Of Nanozymes For Dfu Treatmentmentioning
confidence: 99%
“…In the acute infected wounds, pH is acidic during inflammation, transitioning to a more basic range during granulation and then becoming acidic again during re-epithelialization. A recent study has shown that infected wounds shift from a slightly acidic environment to increased acidification after 24 h due to metabolite production from bacterial proliferation . In contrast, chronic wounds tends to be alkaline, even if acidic metabolites produced by bacterial infection can lower the wound’s pH or render it acidic. , Considering this context, it is conceivable that a pH-responsive hydrogel capable of releasing antimicrobial agents in response to microenvironmental acidification could be applied during the acute phase of an infected wound.…”
Section: Introductionmentioning
confidence: 99%